2006
DOI: 10.1385/endo:29:2:341
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Resistin in the Neonatal Rat: Effects of Dexamethasone and Hypoxia

Abstract: Hypoxia is a common neonatal stress that induces insulin resistance and a decrease in body weight gain. Dexamethasone is often used to treat neonatal cardiopulmonary disease, and also leads to insulin resistance and a decrease in body weight gain. The current study addressed the hypothesis that serum concentrations of the adipokines adiponectin and/or resistin are altered during hypoxia and/or dexamethasone therapy in neonatal rats. Rat pups with their lactating dams were exposed to hypoxia (11% O 2 ) from bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
(45 reference statements)
1
18
0
1
Order By: Relevance
“…For example, hydrocortisone treatment of both obese and normal rats was found to downregulate adiponectin mRNA expression in white adipose tissue, which was also reflected in plasma adiponectin concentrations (Shi et al, 2010). On the other hand, dexamethasone dosing of both normal and hypoxic rats increased plasma adiponectin and similar effects were found in humans (Raff and Bruder, 2006;Jang et al, 2008).…”
Section: Introductionmentioning
confidence: 84%
“…For example, hydrocortisone treatment of both obese and normal rats was found to downregulate adiponectin mRNA expression in white adipose tissue, which was also reflected in plasma adiponectin concentrations (Shi et al, 2010). On the other hand, dexamethasone dosing of both normal and hypoxic rats increased plasma adiponectin and similar effects were found in humans (Raff and Bruder, 2006;Jang et al, 2008).…”
Section: Introductionmentioning
confidence: 84%
“…Very few studies in the clinical literature have examined the effect of OSA or its treatment with nasal continuous positive airway pressure on cortisol levels, although one study suggested that OSA could elevate cortisol levels (41). Another study in neonatal rats has shown that administration of the glucocorticoid dexamethasone can produce a state of relative insulin resistance and mimic the metabolic responses seen with hypoxic exposure (42). Clearly, there is a need for future studies to investigate the relationship between glucocorticoids and potentially other counterregulatory hormones in mediating decreased insulin sensitivity in response to OSA or IH.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that chronic hypoxia in the neonatal rat elicits a multitude of physiological adaptations, including changes in intermediary metabolites and HPA axis function [7,13,15,16,18,20,26,36]. As part of a systematic approach to investigating these adaptations, we have also shown that the lipid composition of pup stomach contents (used as a surrogate for milk composition) was increased considerably during hypoxia [15,16].…”
Section: Discussionmentioning
confidence: 97%
“…Timed-pregnant Sprague-Dawley rats (Harlan Sprague Dawley, Indianapolis, IN; n = 36) were obtained at 14 days gestation and maintained on a standard diet and water ad libitum in a controlled environment (0600-1800 lights on). As soon as a litter was completely delivered, the dam and her pups were immediately moved to an environment chamber and exposed to 21% (normoxia group; n = 14) or 12% (hypoxia group; n = 13) O 2 as described previously [12,13,16,20,36]. Litter size was normalized to 12 pups per litter (mixed sexes).…”
Section: Animal Treatmentmentioning
confidence: 99%
See 1 more Smart Citation